Indirect comparison of SGLT2 inhibitors in patients with established heart failure: evidence based on Bayesian methods - Hai‐Bin Chen; Yao‐Lin Yang; Rong‐Sen Meng; Xue‐Wei Liu (ESC Heart Failure, 2023)
Abstract Aims Head‐to‐head comparisons among SGLT2 inhibitors treatments in established heart failure remain absent. We conducted a systematic review of dedicated heart failure trials to assess indirectly the composite outcomes and individual clinical endpoints among SGLT2 inhibitor treatments. Methods and results We systematically reviewed randomized controlled trials comparing SGLT2 inhibitors versus placebo in patients with established heart failure. A Bayesian approach to network meta‐analysis was applied. Five trials including four treatment strategies were included in this study. The composite of cardiovascular death or hospitalization for heart failure showed no significant difference in the comparison between dapagliflozin and empagliflozin (OR 1.00, 95% CI 0.66–1.55), dapagliflozin and sotagliflozin (OR 1.54, 95% CI 0.91–2.65), and empagliflozin and sotagliflozin (OR 1.53, 95% CI 0.90–2.69). All‐cause mortality showed no significant difference in the comparison between dapagliflozin and empagliflozin (OR 0.92, 95% CI 0.711–1.18), dapagliflozin and sotagliflozin (OR 1.05, 95% CI 0.68–1.59), and empagliflozin and sotagliflozin (OR 1.14, 95% CI 0.74–1.73). Cardiovascular death showed no significant difference in the comparison between dapagliflozin and empagliflozin (OR 0.94, 95% CI 0.71–1.23), dapagliflozin and sotagliflozin (OR 0.96, 95% CI 0.61–1.55), and empagliflozin and sotagliflozin (OR 1.03, 95% CI 0.64–1.66). Hospitalization for heart failure showed no significant difference in the comparison between dapagliflozin and empagliflozin (OR 1.13, 95% CI 0.64–1.97), dapagliflozin and sotagliflozin (OR 1.56, 95% CI 0.74–3.15), and empagliflozin and sotagliflozin (OR 1.39, 95% CI 0.68–2.78). Conclusions In patients with established heart failure, there was no significant difference of the major efficacy outcomes among SGLT2 inhibitor treatments; however, sotagliflozin may be associated with the lowest risk of the composite of cardiovascular death or hospitalization for heart failure, and dapagliflozin may be associated with the lowest risk of all‐cause and cardiovascular mortality.